Effect of Corporate Governance and Capital Adequacy Ratio to Risk in Banks in Asean- 3 - Rizky Mulia; Farah Margaretha Leon; Josephina Endang Purba (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze the effect of corporate governance and the capital adequacy ratio on bank risk. The aspects of corporate governance used are the size of the risk committee, the frequency of meetings of the risk committee, the audit committee, the size of the board of directors, the independence of the board of directors, and institutional ownership, as well as the capital adequacy ratio. Risk variables consist of Credit Risk, Liquidity Risk, and solvency risk. This study also uses asset growth, income diversification, deposit ratio, and government ownership as control variables. The object of research is the banks listed on the Indonesia Stock Exchange, the Malaysia Stock Exchange, and the Thailand Stock Exchange during the 2016-2020 period. This study used purposive sampling method so that 53 banks were obtained as samples. The analytical method used is panel data regression analysis. The results of this study indicate that corporate governance and capital adequacy ratio have significant effect on risk, while the audit committee has no effect on risk. The results of this study provide information that the size of the risk committee, the frequency of risk committee meetings, the size of the board of directors, and institutional ownership can encourage banks to take risks to improve the welfare of shareholders. To control risk, bank managers need to maintain a capital adequacy ratio to absorb risk and investors can encourage the role of independent parties such as risk committees and independent directors to provide input on risk management.